Decentralisation, Decision Space and Directions for Future Research; Comment on "Decentralisation of Health Services in Fiji: A Decision Space Analysis" - Maryam Zahmatkesh; Mark Exworthy (Kerman University of Medical Sciences, 2016)
Decentralisation continues to re-appear in health system reform across the world. Evaluation of these reforms reveals how research on decentralisation continues to evolve. In this paper, we examine the theoretical foundations and empirical references which underpin current approaches to studying decentralisation in health systems.